BLACKBERRY PUBLISHING HOUSE A CASE STUDY ON LEADERSHIP STYLES AND TEAM BUILDING (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Blackberry Publishing House(BPH) is a case  study dealing with a sensitive aspect of human  behaviour,team building and the effects of  Leaders and the leadership process. Working  environment in an organisation largely depends  on the style of Leadership based directly on the  maturity and readiness of the followers. From  Telling style when followers are not willing  not mature to Delegating, when the followers  are willing and very capable,the Leaders have  to articulate the style so that the followers  remain motivated and are encouraged in  achieving their self actualisation. No employee  is working for a job alone,but are looking for  a career and growth. Leaders usually overlook  the aspect of self esteem of an employee and  are result oriented for their advancement. BPH  has a willing lot of workers, but the malaise of  nepotism and strong biases usually dishearten  the employees and who in turn loose interest in  work. Competence of a boss is well appreciated,  but the humane factor in dealing, cannot be  overlooked. The higher management has to  closely monitor the functioning and set the  course right if any deviations are observed,so  that a fair deal is given to all. Opportunist  leaders should be well avoided, as their reliabilty  becomes questionable,and can abandon a ship  again at the time of peril. BPH has a competent  lot of working professional who have a desire  to excel and produce quality work. Lack of  opportunity to showcase their efforts because  of personal differences show poor professional  working, and which cannot be compensated  by verbal motivation. Challenging job, rewards  and recognition, necessarily not monetarily is  a shot- in- the -arm of any employee. Worklife  balance has also been playing an important  role in the lives of employees and if the same is  not maintained, it has a retograde effect on the  motivation of employees and results in severe  stress,which may culminate in an employee  taking an extreme step of quitting the job.  Higher Management,quintessentially, plays a  pivotal role of ensuring fair play, good working  ethics and just that Eustress which makes  the employee working and feeling a sense of  achievement and satisfaction.
Keywords: Blackberry; environment; articulate